ANALYSIS OF THE USE OF AUGMENTED REALITY IN FLAT SURFACE BUILDING MATERIALS - Andreas, Jovan; nanda kuncara , Faatihah; tirta safitri , Prahesti (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2022)
One of the technologies that has been widely used is Augmented Reality (AR). In this study, the author discusses an Augmented Reality application related to the world of education. One of the roles of AR in the world of education is in the process of increasing interest in learning. The nature of AR is to help users more easily recognize an object or thing in 3D form, but there are still many ordinary people who do not know the limitations of its use. To support this, an Augmented Reality application is needed that can provide support for the appropriate research process. The AR research process uses a blackbox table that includes button checking, camera distance, and angle. The author designed an Augmented Reality application using the waterfall method. The research was conducted by finding the minimum camera range distance, minimum camera range angle, and minimum light on the marker on three Android devices to determine the optimal alternative.